A framework for large-scale risk assessment of road-related impacts, with application to mustelids - Fernando Ascensão; Rafael Barrientos; Marcello D’Amico (Global Ecology and Conservation)
Roads, while crucial for human development and economic growth, pose significant threats to biodiversity. Large-scale road risk assessments are essential for guiding infrastructure planning, particularly in identifying areas to avoid new construction or prioritizing regions for mitigation where road networks are already established. However, conducting comprehensive assessments is challenging in regions with limited data on species’ responses to roads. In this study, we propose a methodological approach for global and regional risk assessments of road-related impacts, utilizing data on road exposure and species-level susceptibility to road effects. We first derive species-specific susceptibility to road impacts using available trait data and expert knowledge. This information is spatialized through species range maps, creating a cross-taxa susceptibility layer. We then combine this layer with infrastructure density data to produce a bivariate map that highlights the co-occurrence of susceptibility and exposure. Through this approach, we identify priority mitigation areas—regions with high susceptibility and high exposure where mitigation efforts should be concentrated—and priority preservation areas—regions with high susceptibility but low exposure that should be protected from further road development. Our case-study focuses on mustelids, a globally distributed group with significant vulnerability to road impacts yet underrepresented in road ecology studies. The results reveal that the highest-risk areas are concentrated in Eastern Europe, Southeast Asia, and scattered across sub-Saharan Africa, where high conservation value intersects with extensive road networks, marking these as priority mitigation areas. Priority preservation areas span mainly across South America, North America, and Siberia, with some areas across Africa and Borneo. This framework offers a foundation for preliminary assessments and proactive zoning, aiding in the identification of conservation management areas across different infrastructure types and taxa. Its adaptability makes it a valuable tool for researchers, wildlife managers, and transportation planners conducting large-scale assessments of infrastructure impacts on biodiversity.